Land Disputes in Places of Worship: A Conflict Study - Nurcahya, Yan; Sugiarto, Deri; Maulana, Ilham; Putra, M. Zikril Oksa; Hambaliana, Dandie (UIN Sunan Gunung Djati Bandung, 2024)
This study aims to investigate the land dispute involving the Nurul Ikhlas Mosque in Bandung, West Java, which is listed as a cultural heritage building, and its impact on the social and religious life of the surrounding community. This research uses a qualitative approach with data collection techniques including interviews with local residents, the Head of the Neighborhood Association (RW), the Head of the Mosque Management Board (DKM) of the Nurul Ikhlas Mosque, and field observations. Secondary data is also gathered from related documents, media reports, and relevant literature. The findings show that the land dispute is not only related to land rights but also has significant social impacts on the community, such as the loss of cultural and social identity due to the mosque's demolition. Furthermore, this study reveals the discrepancy between land law, which prioritizes legal and economic aspects, and the need to preserve cultural heritage buildings that hold social and religious value. This research contributes to a deeper understanding of land law application in the context of cultural preservation and religious identity and highlights the importance of a more holistic approach to resolving land disputes involving cultural heritage buildings. This study opens the discussion for more inclusive policies that consider social and cultural aspects in land dispute resolutions.